The meiotic-specific Mek1 kinase in budding yeast regulates interhomolog recombination and coordinates meiotic progression with double strand break repair - Hollingsworth, Nancy M. (Curr Genet, 2019)
Recombination, along with sister chromatid cohesion, is used during meiosis to physically connect homologous chromosomes so that they can be segregated properly at the first meiotic division. Recombination is initiated by the introduction of programmed double strand breaks (DSBs) into the genome, a subset of which are processed into crossovers. In budding yeast, the regulation of meiotic DSB repair is controlled by a meiosis-specific kinase called Mek1. Mek1 kinase activity promotes recombination between homologs, rather than sister chromatids, as well as the processing of recombination intermediates along a pathway that results in synapsis of homologous chromosomes and the distribution of crossovers throughout the genome. In addition, Mek1 kinase activity provides a readout for the number of DSBs in the cell as part of the meiotic recombination checkpoint. This checkpoint delays entry into the first meiotic division until DSBs have been repaired by inhibiting the activity of the meiosis-specific transcription factor Ndt80, a site-specific DNA binding protein that activates transcription of over 300 target genes. Recent work has shown that Mek1 binds to Ndt80 and phosphorylates it on multiple sites, including the DNA binding domain, thereby preventing Ndt80 from activating transcription. As DSBs are repaired, Mek1 is removed from chromosomes and its activity decreases. Loss of the inhibitory Mek1 phosphates and phosphorylation of Ndt80 by the meiosis-specific kinase, Ime2, promote Ndt80 activity such that Ndt80 transcribes its own gene in a positive feedback loop, as well as genes required for the completion of recombination and entry into the meiotic divisions. Mek1 is therefore the key regulator of meiotic recombination in yeast.